+0

# Need help again LOL

0
1372
1
+73

If

C=G - 3F

find the trinomial that represents C when F= 2x2 + 6x - 5 and G=3x2 + 4

Nov 15, 2019

### Best Answer

#1
+9464
+1

C  =  G - 3F

when

=  2x2+ 6x - 5

and  G = 3x2 + 4

So we just have to substitute   2x2+ 6x - 5   in for   F   and   3x2 + 4   in for   G

C  =  G - 3F

C  =  (3x2 + 4) - 3(2x2+ 6x - 5)

C  =  (3x2 + 4) - 3(2x2+ 6x - 5)

The next steps are to simplify expression.

First distribute the negative three to the terms in the parenthesees.

Second combine like terms.

Nov 15, 2019
edited by hectictar  Nov 15, 2019

### 1+0 Answers

#1
+9464
+1
Best Answer

C  =  G - 3F

when

=  2x2+ 6x - 5

and  G = 3x2 + 4

So we just have to substitute   2x2+ 6x - 5   in for   F   and   3x2 + 4   in for   G

C  =  G - 3F

C  =  (3x2 + 4) - 3(2x2+ 6x - 5)

C  =  (3x2 + 4) - 3(2x2+ 6x - 5)

The next steps are to simplify expression.

First distribute the negative three to the terms in the parenthesees.

Second combine like terms.

hectictar Nov 15, 2019
edited by hectictar  Nov 15, 2019